Open partial or transoral laryngectomy – total laryngectomy today - Thurnher, Dietmar; Simo, Ricard; Succo, Giovanni; Vilaseca, Isabel; Simon, Christian (Frontiers in Oncology, 2025)
Total laryngectomy, a surgical procedure involving the complete removal of the larynx, has been a crucial treatment for advanced laryngeal cancer since its introduction in 1873. Over the past 150 years, this procedure has evolved significantly, with improvements in surgical techniques, postoperative care, and rehabilitation methods leading to better survival rates and quality of life for patients. While organ-preserving approaches like radiochemotherapy have gained prominence in recent decades, total laryngectomy remains an essential option for cases of advanced cancer or when other treatments fail. This review explores the history, development, and current role of total laryngectomy in treating laryngeal cancer, as well as comparing it to alternative surgical approaches like open partial laryngectomy and transoral laser microsurgery or organ preservation protocols.